Competing Through Experience: The Influence of Word of Mouth, Atmosphere, and Location on Consumer Purchasing Decisions in Kediri’s Gang Skena Cafés - Gonzales, Davana Recxy; Syahputra, Erwin (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of Word of Mouth (WOM), Cafe Atmosphere, and Location on Purchasing Decisions in the Gang Skena Area of ??Kediri City. The phenomenon of increasing numbers of cafes and tight competition requires business actors to understand the factors that determine consumer purchasing decisions. This study uses a quantitative approach by distributing questionnaires to cafe consumers in the Gang Skena area of ??Kediri City. Samples were taken using non-probability sampling techniques, with data analysis using multiple linear regression analysis processed through statistical software. The results of the study indicate that the variables Word of Mouth, Cafe Atmosphere, and Location partially have a positive and significant influence on Purchasing Decisions. Furthermore, simultaneously, the three independent variables (Word of Mouth, Cafe Atmosphere, and Location) together have a significant influence on Purchasing Decisions. The contribution of the influence of the three variables is 68.3%, while the remaining 31.7% is explained by other factors outside this research model. The conclusion of this study is that Word of Mouth, Cafe Atmosphere, and Location are important factors that significantly influence consumer purchasing decisions in cafes in the Gang Skena area of ??Kediri City, both individually and collectively.